PHASE SPACE ANALYSIS OF COSMOLOGICAL MODELS BY NONLINEAR ELECTRODYNAMICS - Nasiroh, Chilwatun
In this thesis, we aim to develop a cosmological model capable of explaining the evolution of the universe from its early to late-time in a continuous manner; primarily encompasses scenarios of inflation and late-time acceleration. Furthermore, we explore anisotropic inflation models to address anomalies in the Cosmic Microwave Background (CMB). Both of these models are examined by proposing a Nonlinear Electrodynamic field (NLED) as a source of gravity. The evolution of the universe is examined by analogizing the equations governing its evolution to the Hamiltonian equations of a particle under the influence of a one-dimensional potential. Phase space analysis of the inflationary model by NLED in anisotropic space-time reveals a critical point in the form of a centre, indicating an Einstein static universe between the inflationary era and late-time deceleration. Anisotropy is starting on small scales, undergoes expansion simultaneously with inflation, generating primordial fluctuations on cosmological scales and ultimately serving as the seeds for the formation of large-scale structures. A cosmological model with a continuous scenario of inflation in the early universe and late-time expansion is developed by investigating the NLED field with non-minimal coupling, supplemented with a cosmological constant. The phase space analysis of this cosmological model yields two critical points: a centre and a saddle. These critical points describe an Einstein static universe. During the early stages of the universe, radiation, in the form of the NLED field, was the dominant factor. As the universe evolved, it transitioned to being predominantly influenced by dark energy towards the end of its evolution.